Esophageal stem cells and genetics/epigenetics in esophageal cancer. (29th September 2014) - Croagh, Daniel; Frede, Julia; Jones, Philip H.; Kaur, Pritinder; Partensky, Christian; Phillips, Wayne A.
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on the relationship between stem cells, cancer, and the esophagus; the behavior of esophageal stem cells; and the role of genetics and epigenetics in approaches to translational research.